Digitalisasi Sistem Pemeriksaan Kendaraan Sebelum Keberangkatan pada Armada Truk Tangki PT Putera Baja Tunggal - Fabian Devara Muchamad; Sugiyarto Sugiyarto (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2026)
Vehicles transporting petrochemical materials have high operational risks and therefore require a pre-trip inspection to ensure that vehicles are roadworthy and safe to operate. At PT Putera Baja Tunggal, the inspection process is still conducted manually using paper-based forms, leading to inefficiencies, potential data loss, and difficulties in archiving and monitoring fleet conditions. This study aims to analyze the existing vehicle inspection process and to design and develop a digital system to support pre-trip inspection activities. The research method used is Research and Development (R&D) with the ADDIE model, which consists of analysis, design, development, implementation, and evaluation stages. The application was developed using the Android-based Kodular platform with Google Drive integration as a data storage system. The results show that the developed digital system improves the effectiveness of the inspection process, accelerates data input, and enhances the organization and security of inspection records. Quantitatively, the application eliminates additional manual data entry time of approximately 4 minutes and improves overall inspection efficiency by more than 40% compared to conventional methods. Therefore, the digitalization of the pre-trip inspection system can better support the operational safety of tanker truck fleets at PT Putera Baja Tunggal.